Corrosion-resistant neodymium-iron-boron magnet and preparation method thereof
By adding alloy nanopowder to the NdFeB magnet and spraying the coating liquid containing zinc and aluminum sheet powder to form a sealing coating, the problem of poor corrosion resistance of NdFeB magnet is solved and its corrosion resistance is significantly improved and magnetic properties.
Patent Information
- Application Number
- CN202411850477.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-14
AI Technical Summary
The existing neodymium iron boron magnets have poor corrosion resistance, especially in long-term high-temperature environments, warm and humid environments and electrochemical environments, resulting in the anti-corrosion layer falling off and unable to effectively protect the magnets.
In the preparation process of neodymium iron boron magnet, alloy nanopowder is added, and a coating liquid containing zinc, aluminum sheet powder and silane is sprayed on its surface to form a sealing coating to prevent the erosion of substances such as oxygen and water.
Through the combination of alloy nanopowder and coating liquid, the corrosion resistance of neodymium iron boron magnets is significantly improved, the bonding strength between the coating is enhanced, the service life of the coating is extended, and the magnet is improved. Overall performance.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of NdFeB magnets, and in particular to a corrosion-resistant NdFeB magnet and a preparation method thereof. Background Art
[0002] NdFeB permanent magnets, with super strong permanent magnetic properties, have been widely used in the fields of electronics, information, communication engineering, automation, aerospace, national defense, energy-saving motors, wind power generation, and electric vehicle lights. However, there are still some disadvantages in the promotion and application of NdFeB magnets, that is, the corrosion resistance of NdFeB magnets is poor, which is caused by the multi-phase structure of the device and the chemical characteristics of each phase. According to the research, the corrosion of NdFeB magnets mainly occurs in three environments, namely, long-term high temperature environment (>150℃), warm and humid environment, and electrochemical environment. Therefore, solving the corrosion problem of NdFeB magnets has become the focus of current research. The fundamental measure for the surface protection of NdFeB magnets is to use coatings to block the erosion of oxygen, moisture or other substances in the air to achieve the purpose of protection.
[0003] The corrosion resistance of NdFeB magnets in the prior art is to compound an aluminum soft alloy layer on the surface of the NdFeB magnet, and then compound one or more aluminum hard alloy layers on the surface of the aluminum soft alloy layer, thereby improving the corrosion resistance of the NdFeB magnet.
[0004] However, the surface strength of the aluminum alloy layer in this method is low, and its bonding force with the surface of the NdFeB magnet is low, and the anti-corrosion layer is prone to fall off, thereby failing to effectively protect the NdFeB magnet. Summary of the invention
[0005] In order to improve the anti-corrosion performance of NdFeB magnets, the present invention provides a corrosion-resistant NdFeB magnet and a preparation method thereof.
[0006] The first aspect of the present invention is to provide a method for preparing a corrosion-resistant NdFeB magnet, which adopts the following technical scheme: A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Evenly mix the NdFeB powder obtained by jet milling with the alloy nanopowder, and sieve to obtain a mixed material, wherein the amount of the alloy nanopowder added is 0.2-0.8% by weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and molding, sintering the compact to obtain a NdFeB magnet; S4, pre-treating the NdFeB magnet; S5. Prepare a coating liquid, stir and mix silane, solvent and water in a weight ratio of 1: (0.8-1.2): (2.2-2.8) to prepare a silane hydrolyzate, then add zinc and aluminum flake powders, stir and mix evenly, spray, and then dry to obtain a corrosion-resistant NdFeB magnet.
[0007] Preferably, the weight ratio of the zinc and aluminum flake powders is 3:1.
[0008] Preferably, the coating liquid also includes epoxy resin, curing agent and diluent in the preparation, the weight ratio of the epoxy resin added to the total amount of zinc and aluminum flake powder is 0.5: (1-1.5), and the amount of the curing agent and diluent added is 0.2% of the weight of the epoxy resin.
[0009] Preferably, the sintering process is: raise the temperature to 1050-1100°C and keep it for 2-3 hours, introduce inert gas, cool it down to below 50°C by air cooling, then raise the temperature to 940-980°C for a tempering treatment, keep it for 1.5 hours, then cool it down to 440-480°C for a secondary tempering treatment, and keep it for 2 hours.
[0010] Preferably, the alloy nanopowder is one or both of copper-aluminum alloy powder and holmium-aluminum alloy powder.
[0011] Preferably, the weight ratio of the copper-aluminum alloy powder to the holmium-aluminum alloy powder is 1:(1-1.3).
[0012] Preferably, the weight ratio of holmium to aluminum in the holmium-aluminum alloy powder is 7:3.
[0013] Preferably, the weight ratio of copper to aluminum in the copper-aluminum alloy powder is 8:2.
[0014] Preferably, the NdFeB powder is surface treated by adding 1-5wt% of a silane coupling agent to a solvent, then adding the NdFeB powder, stirring and mixing, and then heating and drying to obtain coupling agent-coated NdFeB powder. The amount of the solvent is sufficient to immerse the NdFeB powder.
[0015] The second aspect of the present invention provides a corrosion-resistant NdFeB magnet obtained by the above-mentioned method for preparing the corrosion-resistant NdFeB magnet.
[0016] In summary, the present invention has the following beneficial effects: 1. The present application adds alloy nanopowder in the preparation of NdFeB magnets, which can effectively improve the corrosion resistance of NdFeB magnets themselves. After spraying the coating liquid on the NdFeB magnets, the aluminum-zinc sheets in the coating liquid form a coating on the NdFeB magnets, which effectively seals the pores and cracks on the surface of the NdFeB magnets, thereby effectively isolating the NdFeB magnets from the erosion of oxygen, moisture and other substances in the air, thereby improving the corrosion resistance of the NdFeB magnets. In addition, the corrosion products formed during the corrosion of aluminum and zinc further fill the pores and cracks, hinder the movement of the corrosive medium, and further improve the corrosion resistance of the NdFeB magnets. Moreover, the addition of silane can improve the bonding performance between the aluminum and zinc sheets and the NdFeB magnets, and improve the service life of the coating.
[0017] 2. When the alloy powder is selected as a combination of copper-aluminum and gold powder and holmium-aluminum alloy powder, the NdFeB magnet can be effectively densified, the pores inside the NdFeB magnet can be reduced, and the corrosion resistance of the NdFeB magnet can be improved. In addition, the densification of the magnet can further improve the magnetic properties of the NdFeB magnet.
[0018] 3. The addition of epoxy resin in the coating liquid combines with the NdFeB powder coated with silane coupling agent, which effectively improves the bonding strength between the coating and the NdFeB magnet, thereby further improving the service life of the coating and ensuring that the NdFeB magnet has good corrosion resistance. DETAILED DESCRIPTION
[0019] The present invention is further described in detail below with reference to the embodiments.
[0020] The raw materials used in this application are all commercially available.
[0021] Example 1 A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Prepare materials according to the ratio of (PrNd)30DyFe66.24CoAl0.6Cu0.2B0.96 and perform smelting to obtain a main NdFeB alloy ingot, which is then placed in a smelting belt-spinning system to obtain a NdFeB belt-spinning sheet, and then treated with hydrogen explosion and air flow milling, and then the NdFeB powder and the alloy nanopowder are evenly mixed, and a mixed material is obtained after sieving through 300 meshes, wherein the alloy nanopowder adopts copper-aluminum alloy powder (the weight ratio of copper to aluminum is 8:2), and the addition amount is 0.2% of the weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and forming, sintering the pressed green sheet to obtain NdFeB magnets, the sintering process is: raising the temperature to 1050°C and then keeping it at that temperature for 3 hours, introducing inert gas, cooling it to below 50°C by air cooling, then raising the temperature to 940°C for a tempering treatment, keeping it at that temperature for 1.5 hours, then cooling it to 440°C for a secondary tempering treatment, keeping it at that temperature for 2 hours; S4, pre-treating the NdFeB magnet, the pre-treatment comprising grinding the surface of the NdFeB magnet, then ultrasonically washing it, and drying it for standby use; S5. Prepare coating liquid. The total amount of silane hydrolyzate is 100 kg. Silane, solvent (ethanol) and water are stirred and mixed in a weight ratio of 1:0.8:2.2 to prepare silane hydrolyzate, i.e. 25 kg of silane, 20 kg of solvent and 55 kg of water. Add 40 kg of zinc and aluminum flake powders to the silane hydrolyzate, stir and mix evenly, then spray. Bake at 230°C for 45 min to obtain corrosion-resistant NdFeB magnets, in which the weight ratio of zinc and aluminum flake powders is 3:1.
[0022] Example 2 A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Prepare materials according to the ratio of (PrNd)30DyFe66.24CoAl0.6Cu0.2B0.96 and perform smelting to obtain a main NdFeB alloy ingot, which is then placed in a smelting belt-spinning system to obtain a NdFeB belt-spinning sheet, and then hydrogen explosion and air flow milling are performed, and the NdFeB powder and the alloy nanopowder are evenly mixed, and a mixed material is obtained after sieving through 300 meshes, wherein the addition amount of the alloy nanopowder is 0.5% of the weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and forming, sintering the pressed green sheet to obtain NdFeB magnets, the sintering process is: raising the temperature to 1080°C and then keeping it at that temperature for 3 hours, introducing inert gas, cooling it to below 50°C by air cooling, then raising the temperature to 960°C for a tempering treatment, keeping it at that temperature for 1.5 hours, then cooling it to 460°C for a secondary tempering treatment, keeping it at that temperature for 2 hours; S4, pre-treating the NdFeB magnet, the pre-treatment comprising grinding the surface of the NdFeB magnet, then ultrasonically washing it, and drying it for standby use; S5. Prepare coating liquid. The total amount of silane hydrolyzate is 100 kg. Silane, solvent (ethanol) and water are stirred and mixed in a weight ratio of 1:0.8:2.2 to prepare silane hydrolyzate, i.e. 25 kg of silane, 20 kg of solvent and 55 kg of water. Add 40 kg of zinc and aluminum flake powders to the silane hydrolyzate, stir and mix evenly, then spray. Bake at 230°C for 45 min to obtain corrosion-resistant NdFeB magnets, in which the weight ratio of zinc and aluminum flake powders is 3:1.
[0023] Example 3 A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Prepare materials according to the ratio of (PrNd)30DyFe66.24CoAl0.6Cu0.2B0.96 and perform smelting to obtain a main NdFeB alloy ingot, which is then placed in a smelting belt-spinning system to obtain a NdFeB belt-spinning sheet, and then hydrogen explosion and air flow milling are performed, and the NdFeB powder and the alloy nanopowder are evenly mixed, and a mixed material is obtained after sieving through 300 meshes, wherein the addition amount of the alloy nanopowder is 0.8% of the weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and forming, sintering the pressed green sheet to obtain NdFeB magnets, the sintering process is: raising the temperature to 1100°C and keeping it for 2 hours, introducing inert gas, cooling it to below 50°C by air cooling, then raising the temperature to 980°C for a tempering treatment, keeping it for 1.5 hours, then cooling it to 480°C for a secondary tempering treatment, keeping it for 2 hours; S4, pre-treating the NdFeB magnet, the pre-treatment comprising grinding the surface of the NdFeB magnet, then ultrasonically washing it, and drying it for standby use; S5. Prepare coating liquid. The total amount of silane hydrolyzate is 100 kg. Silane, solvent (ethanol) and water are stirred and mixed in a weight ratio of 1:0.8:2.2 to prepare silane hydrolyzate, i.e. 25 kg of silane, 20 kg of solvent and 55 kg of water. Add 40 kg of zinc and aluminum flake powders to the silane hydrolyzate, stir and mix evenly, then spray. Bake at 230°C for 45 min to obtain corrosion-resistant NdFeB magnets, in which the weight ratio of zinc and aluminum flake powders is 3:1.
[0024] Example 4 A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Prepare materials according to the ratio of (PrNd)30DyFe66.24CoAl0.6Cu0.2B0.96 and perform smelting to obtain a main NdFeB alloy ingot, which is then placed in a smelting belt-spinning system to obtain a NdFeB belt-spinning sheet, and then hydrogen explosion and air flow milling are performed, and the NdFeB powder and the alloy nanopowder are evenly mixed, and a mixed material is obtained after sieving through 300 meshes, wherein the addition amount of the alloy nanopowder is 0.5% of the weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and forming, sintering the pressed green sheet to obtain NdFeB magnets, the sintering process is: raising the temperature to 1080°C and then keeping it at that temperature for 3 hours, introducing inert gas, cooling it to below 50°C by air cooling, then raising the temperature to 960°C for a tempering treatment, keeping it at that temperature for 1.5 hours, then cooling it to 460°C for a secondary tempering treatment, keeping it at that temperature for 2 hours; S4, pre-treating the NdFeB magnet, the pre-treatment comprising grinding the surface of the NdFeB magnet, then ultrasonically washing it, and drying it for standby use; S5. Prepare coating liquid. The total amount of silane hydrolyzate is 100 kg. Silane, solvent (ethanol) and water are stirred and mixed in a weight ratio of 1:1:2.5 to prepare silane hydrolyzate, i.e. 22 kg of silane, 22 kg of solvent and 56 kg of water. Add 40 kg of zinc and aluminum flake powder to the silane hydrolyzate, stir and mix evenly, then spray. Bake at 230°C for 45 min to obtain corrosion-resistant NdFeB magnets, wherein the weight ratio of zinc to aluminum flake powder is 3:1.
[0025] Example 5 A method for preparing a corrosion-resistant NdFeB magnet comprises the following steps: S1. Prepare materials according to the ratio of (PrNd)30DyFe66.24CoAl0.6Cu0.2B0.96 and perform smelting to obtain a main NdFeB alloy ingot, which is then placed in a smelting belt-spinning system to obtain a NdFeB belt-spinning sheet, and then hydrogen explosion and air flow milling are performed, and the NdFeB powder and the alloy nanopowder are evenly mixed, and a mixed material is obtained after sieving through 300 meshes, wherein the addition amount of the alloy nanopowder is 0.5% of the weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and forming, sintering the pressed green sheet to obtain NdFeB magnets, the sintering process is: raising the temperature to 1080°C and then keeping it at that temperature for 3 hours, introducing inert gas, cooling it to below 50°C by air cooling, then raising the temperature to 960°C for a tempering treatment, keeping it at that temperature for 1.5 hours, then cooling it to 460°C for a secondary tempering treatment, keeping it at that temperature for 2 hours; S4, pre-treating the NdFeB magnet, the pre-treatment comprising grinding the surface of the NdFeB magnet, then ultrasonically washing it, and drying it for standby use; S5. Prepare coating liquid. The total amount of silane hydrolyzate is 100 kg. Silane, solvent (ethanol) and water are stirred and mixed in a weight ratio of 1:1.2:2.8 to prepare silane hydrolyzate, i.e. 20 kg of silane, 24 kg of solvent and 56 kg of water. Add 40 kg of zinc and aluminum flake powder to the silane hydrolyzate, stir and mix evenly, then spray. Bake at 230°C for 45 min to obtain corrosion-resistant NdFeB magnets, in which the weight ratio of zinc and aluminum flake powder is 3:1.
[0026] Example 6 A method for preparing a corrosion-resistant NdFeB magnet, which differs from Example 4 in that an equal amount of holmium-aluminum alloy powder (the mass ratio of holmium to aluminum is 7:3) is used instead of copper-aluminum alloy powder, and the rest is the same as Example 4.
[0027] Example 7 A method for preparing a corrosion-resistant NdFeB magnet, which is different from Example 4 in that the alloy nanopowder includes holmium aluminum alloy powder and copper aluminum alloy powder in a weight ratio of 1:1, and the rest is the same as Example 4.
[0028] Example 8 A method for preparing a corrosion-resistant NdFeB magnet, which is different from Example 4 in that the alloy nanopowder includes holmium aluminum alloy powder and copper aluminum alloy powder in a weight ratio of 1.3:1, and the rest is the same as Example 4.
[0029] Example 9 A method for preparing a corrosion-resistant NdFeB magnet, which is different from Example 7 in that, in step S5, in preparing a coating liquid, the total amount of silane hydrolyzate is 100 kg, silane, solvent (using ethanol) and water are stirred and mixed in a weight ratio of 1:1:2.5 to prepare a silane hydrolyzate, i.e., 22 kg of silane, 22 kg of solvent and 56 kg of water, 40 kg of zinc and aluminum flaky powders, epoxy resin, dicyandiamide and diluent (alkylene glycidyl ether) are added to the silane hydrolyzate, stirred and mixed evenly, sprayed, and baked at 230°C for 45 minutes to obtain a corrosion-resistant NdFeB magnet, wherein the weight ratio of zinc and aluminum flaky powders is 3:1, and the weight ratio of epoxy resin to the total amount of zinc and aluminum powders is 0.5:1, i.e., the amount of epoxy resin is 20 kg, the amount of dicyandiamide added is 4 kg, and the amount of diluent (alkylene glycidyl ether) added is 4 kg.
[0030] Example 10 A method for preparing a corrosion-resistant NdFeB magnet, which is different from Example 7 in that, in step S5, in preparing a coating liquid, the total amount of silane hydrolyzate is 100 kg, silane, solvent (using ethanol) and water are stirred and mixed in a weight ratio of 1:1:2.5 to prepare a silane hydrolyzate, i.e., 22 kg of silane, 22 kg of solvent and 56 kg of water, 40 kg of zinc and aluminum flaky powders, epoxy resin, dicyandiamide and diluent (alkylene glycidyl ether) are added to the silane hydrolyzate, stirred and mixed evenly, sprayed, and baked at 230°C for 45 minutes to obtain a corrosion-resistant NdFeB magnet, wherein the weight ratio of zinc and aluminum flaky powders is 3:1, and the weight ratio of epoxy resin to the total amount of zinc and aluminum powders is 0.5:1.5, i.e., the amount of epoxy resin is 13 kg, the amount of dicyandiamide added is 2.6 kg, and the amount of diluent (alkylene glycidyl ether) added is 2.6 kg.
[0031] Embodiment 11 A method for preparing a corrosion-resistant NdFeB magnet is different from Example 9 in that the NdFeB powder obtained by air flow milling is surface treated, and the matrix is prepared by adding 1wt% of a silane coupling agent to ethanol, and then adding the NdFeB powder to stir and mix evenly, followed by heating and drying to obtain a coupling agent-coated NdFeB powder, wherein the amount of solvent is required to immerse the NdFeB powder.
[0032] Example 12 A method for preparing a corrosion-resistant NdFeB magnet is different from Example 9 in that the NdFeB powder obtained by air flow milling is surface treated, and the matrix is prepared by adding 3wt% of a silane coupling agent to ethanol, and then adding the NdFeB powder, stirring and mixing evenly, and then heating and drying to obtain a coupling agent-coated NdFeB powder, wherein the amount of solvent is required to immerse the NdFeB powder.
[0033] Embodiment 13 A method for preparing a corrosion-resistant NdFeB magnet is different from Example 9 in that the NdFeB powder obtained by air flow milling is surface treated, and the matrix is prepared by adding 5wt% of a silane coupling agent to ethanol, and then adding the NdFeB powder to stir and mix evenly, followed by heating and drying to obtain a coupling agent-coated NdFeB powder, wherein the amount of solvent is required to immerse the NdFeB powder.
[0034] Comparative Example 1 A method for preparing a corrosion-resistant NdFeB magnet is different from that of Example 4 in that only zinc flake powder is added to the coating liquid, and the rest is the same as that of Example 4.
[0035] Comparative Example 2 A method for preparing a corrosion-resistant NdFeB magnet is different from Example 4 in that only aluminum flake powder is added to the coating liquid, and the rest is the same as Example 4.
[0036] Performance Testing The corrosion resistance of the NdFeB magnets obtained in the above examples was tested, and the test results are shown in Table 1.
[0037] The corrosion resistance test is carried out by conducting a neutral salt spray test to measure the duration of the salt spray test when the sample reaches the same degree of corrosion. The salt spray test conditions are: the test chamber temperature is 37°C, the volume concentration of the salt water is 5%, and the test method is continuous spray.
[0038] The samples obtained in the above examples and comparative examples were subjected to a scraping test by using 100-mesh sandpaper at 50 N / cm 2 The samples were scraped under a pressure of , and the degree of damage to the sample coating was observed. The degree of damage was defined as follows: Level 1: 1-2 scratches; Level 2: 3-4 scratches; Level 3: 5-6 scratches; Level 4: 7-9 scratches; Level 5: scratches above level 10.
[0039] Table 1 NdFeB magnet performance test results Test items Example 1 Example 2 Example 3 Example 4 Example 5 Salt spray test duration / h 960 965 964 972 970 Damage level / grade Level 2 Level 2 Level 2 Level 2 Level 2 Test items Example 6 Example 7 Example 8 Example 9 Example 10 Salt spray test duration / h 972 9778 975 985 983 Damage level / grade Level 2 Level 2 Level 2 Level 1 Level 1 Test items Embodiment 11 Example 12 Embodiment 13 Comparative Example 1 Comparative Example 2 Salt spray test duration / h 988 991 990 942 940 Damage level / grade No scratches No scratches No scratches Level 3 Level 3 From the table above we can see that: The corrosion-resistant NdFeB magnets obtained in Examples 1-13 of the present application have a neutral salt spray test duration of greater than or equal to 960 h, which is much higher than the corrosion-resistant NdFeB magnets obtained in Comparative Examples 1 and 2. In addition, in the scraping test of the corrosion-resistant NdFeB magnets obtained in the examples of the present application, the degree of damage is less than or equal to level 2, and the NdFeB magnets obtained in Examples 11-13 have no scratches. It can be seen that the bonding strength between the coating of the present application and the NdFeB magnet is relatively high, and the formed coating also has good mechanical properties, which effectively improves the protective performance of the coating on the NdFeB magnet. In Comparative Examples 1 and 2, when only zinc flake powder or aluminum flake powder is added to the coating liquid, the degree of damage of the NdFeB magnets obtained in Comparative Examples 1 and 2 in the scraping test is significantly increased compared to Example 4. It can be seen that the combined use of aluminum flake powder, zinc flake powder and silane hydrolyzate can not only effectively improve the corrosion resistance of NdFeB magnets, but also improve the bonding performance between NdFeB magnets and the coating, effectively ensuring the protective effect of the coating on NdFeB magnets.
[0040] The embodiments of the specific implementation methods are all preferred embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Therefore, any equivalent changes made based on the structure, shape, and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a corrosion-resistant NdFeB magnet, characterized in that: The steps include: S1. Evenly mix the NdFeB powder obtained by jet milling with the alloy nanopowder, and sieve to obtain a mixed material, wherein the amount of the alloy nanopowder added is 0.2-0.8% by weight of the NdFeB powder; S2, compression molding, the mixed material is subjected to compression molding and oil isostatic pressing to obtain a compact; S3, sintering and molding, sintering the compact to obtain a NdFeB magnet; S4, pre-treating the NdFeB magnet; S5. Prepare a coating liquid, stir and mix silane, solvent and water in a weight ratio of 1: (0.8-1.2): (2.2-2.8) to prepare a silane hydrolyzate, then add zinc and aluminum flake powders, stir and mix evenly, then spray, and then dry to obtain a corrosion-resistant NdFeB magnet.
2. The method for preparing a corrosion-resistant NdFeB magnet according to claim 1, characterized in that: The weight ratio of the zinc and aluminum flake powders is 3:
1.
3. The method for preparing a corrosion-resistant NdFeB magnet according to claim 1, characterized in that: The coating liquid also includes epoxy resin, curing agent and diluent in the preparation. The weight ratio of the epoxy resin to the total amount of zinc and aluminum flake powder is 0.5: (1-1.5). The curing agent and diluent are both added in an amount of 0.2% of the weight of the epoxy resin.
4. The method for preparing a corrosion-resistant NdFeB magnet according to claim 1, characterized in that: The sintering process is as follows: the temperature is raised to 1050-1100°C and kept at this temperature for 2-3 hours, an inert gas is introduced, the temperature is cooled to below 50°C by air cooling, the temperature is raised to 940-980°C for a tempering treatment, kept at this temperature for 1.5 hours, and then the temperature is lowered to 440-480°C for a secondary tempering treatment, kept at this temperature for 2 hours.
5. The method for preparing a corrosion-resistant NdFeB magnet according to claim 1, characterized in that: The alloy nano powder is one or both of copper-aluminum alloy powder and holmium-aluminum alloy powder.
6. The method for preparing a corrosion-resistant NdFeB magnet according to claim 5, characterized in that: The weight ratio of the copper-aluminum alloy powder to the holmium-aluminum alloy powder is 1:(1-1.3).
7. The method for preparing a corrosion-resistant NdFeB magnet according to claim 5, characterized in that: The weight ratio of holmium to aluminum in the holmium-aluminum alloy powder is 7:
3.
8. The method for preparing a corrosion-resistant NdFeB magnet according to claim 5, characterized in that: The weight ratio of copper to aluminum in the copper-aluminum alloy powder is 8:
2.
9. The method for preparing a corrosion-resistant NdFeB magnet according to claim 1, characterized in that: The NdFeB powder is surface treated by adding 1-5wt% of silane coupling agent to a solvent, then adding the NdFeB powder, stirring and mixing evenly, and then heating and drying to obtain coupling agent-coated NdFeB powder. The amount of the solvent is required to immerse the NdFeB powder.
10. A corrosion-resistant NdFeB magnet obtained by the method for preparing a corrosion-resistant NdFeB magnet according to any one of claims 1 to 9.
Citation Information
Cited By
Corrosion-resistant powerful magnet material and preparation method thereof
CN120015455A
A corrosion-resistant high-strength magnet material and its preparation method
CN120015455B